2013
DOI: 10.30970/cma6.0272
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier transfer in amorphous (GeS)1-хBiх films

Abstract: The influence of Bi additions on the electrical and photoelectrical properties of amorphous (GeS) 1-х Bi х films (0 ≤ ≤ ≤ ≤ х ≤ ≤ ≤ ≤ 0.15) has been investigated. Adding Bi to amorphous GeS condensates leads to changes in the mechanism of conductivity and inversion of the conductivity type. Bi-additives reduce the activation energy of photoconductivity and photosensitivity of the GeS films. The changes of the physical properties of the films are explained considering a heterogeneous structure of the condensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The band gap of amorphous GeS can be determined to be 1.50 eV by linear fitting of the near absorption edge in the Tauc plot, (αhν) 1/2 as a function of photon energy hν displayed in Fig. 4a, where α is the absorption coefficient, which is consistent with the reported one 25 . A 0.116 eV energy of Urbach tail (E u ), known as the width of the localized band tail, can also be obtained by fitting the α versus hν.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The band gap of amorphous GeS can be determined to be 1.50 eV by linear fitting of the near absorption edge in the Tauc plot, (αhν) 1/2 as a function of photon energy hν displayed in Fig. 4a, where α is the absorption coefficient, which is consistent with the reported one 25 . A 0.116 eV energy of Urbach tail (E u ), known as the width of the localized band tail, can also be obtained by fitting the α versus hν.…”
Section: Resultssupporting
confidence: 84%
“…Noticeably, the hybridization of S-based Ge alloy presents 15% larger than that of Te-based Ge alloy, enabling large ON current. Moreover, the sharp increase of band gap (GeTe 6 0.6 eV 24 , GeSe 1.0 eV 15 , GeS 1.5 eV 25 ) is beneficial for achieving low OFF current and therefore larger selectivity. As smaller covalent radius also leads to stronger bonds with Ge atom (bond energy: Te-Ge 192 kJ mol −1 , Se-Ge 234 kJ mol −1 , S-Ge, 266 kJ mol −1 ), and an increase of the crystallization temperature would be expected to minimize the undesired crystallization.…”
mentioning
confidence: 99%
“…As the most representative element in the chalcogen, the 16th element sulfur (S) has been the subject of numerous investigations, regarding its crystal structure [84][85][86][87][88][89], electronic structure [84,85,[90][91][92], thermodynamic properties [84], and other physical characteristics (Fig. 17a).…”
Section: S-based Otsmentioning
confidence: 99%
“…In 2020, Jia et al first reported S-based OTS materials [66], GeS, and then Ge-S alloys were systematically studied. Since the atomic radius of S atoms was just 0.88 Å, > 0.3 Å smaller than Se and Te atoms, the Ge-S compounds exhibited high crystallization temperatures, 380 °C for GeS and exceeding 600 °C for GeS 2 [92]. The mobility gap of Ge-S system increased with an elevated concentration of S, for S-rich Ge-S, the mobility gap ranged from 2.6 V to 3.4 eV and it could reach 3.8 eV in pure S (Fig.…”
Section: S-based Otsmentioning
confidence: 99%